Arm Robot 5-DOF using Matlab GUI Text Commands - Arnan, Arnan; Basri, Muhammad; Syafar, A. Muhammad (Universitas Medan Area, 2025)
This research explores the relationship between Matlab programming language and robot arm control through string or word commands. Experiments were conducted with various commands to move the robot arm in the desired direction. The implementation of this system was tested on a robot arm equipped with a unique gripper for grasping and moving test tubes. Experimental results show that the system can recognize GUI text commands with a high accuracy of 98% in providing direction/action to the test tube according to the instructions given. Thus, incorporating the robot arm control method through string or word commands in the development of this system contributes positively to the precision and responsiveness of the robot arm control system. This research opens up opportunities for further growth in robotics, especially in chemical laboratory applications, where manipulating sensitive materials requires highly accurate control. The successful use of string or word commands in controlling robots offers the potential for widespread implementation in various fields that need responsive and efficient human-machine interaction. This study contributes to the robotics and automation development literature, combining chemical robot technology and Matlab to improve robot controllability. The results show that Matlab with string/word commands can effectively control the robot arm